Kemampuan Akademik Peserta Ujian Kompetensi Sekolah Menengah Kejuruan - Korosando, Fransiskus; Raji, Maggu Ngguna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to describe the parameters of the question item in the instrument of the eye competency exam of the training of package A and package B, as well as to describe the ability of the competency test participants of vocational school students in Ende Regency. This research uses a type of quantitative research with an ex-post facto approach. The data is obtained by documentation technique, which is to quote the test takers' answers on the answer sheet, and analyzed using a classic test theory approach. The results of the analysis showed that the accounting training eye test devices of Package A and Package B most of the problem items prepared did not meet the